KEARIFAN LOKAL PADA GAYA WACANA DALAM NOVEL RONGGENG DUKUH PARUK KARYA AHMAD TOHARI: KAJIAN STILISTIKA - Nugrahani, Farida; Al-Ma’ruf, Ali Imron (Prosiding Seminar Nasional dan Internasional HISKI, 2024)
This research aims to (1) describe discourse as a form of Ronggeng Dukuh Paruk (RDP) stylistics and (2) reveal the function and purpose of using discourse style as an author's expression in expressing ideas about the local wisdom of Java, Banyumas. The research method is descriptive qualitative which prioritizes nuanced interpretations. The data is in the form of words, sentences and discourse in the RDP novel which contains local Javanese wisdom. The data source is the RDP novel. Data collection was carried out by literature study. Data analysis was carried out by applying the Semiotic model reading method, namely heuristics and hermeneutics and the inductive thinking method. The results of the RDP stylistic study show: (1) the discourse style in RDP is unique and distinctive, namely the code-switching discourse style in Javanese and at the same time proves Tohari's competence in empowering all language potential; (2) the code-switching discourse style in Javanese is used to display traditional Javanese mantras and songs (songs) that are rich in variations in order to expose the local wisdom of Java, Banyumas.